Comparison in Measuring Effectiveness of Momentum and Contrarian Trading Strategy in Indonesian Stock Exchange - Luxianto, Rizky (UI Scholars Hub, 2011)
This paper wants to explore the effectiveness of momentum or contrarian strategy in Indonesian Stock Exchange using different methods in measuring the performance. The point of momentum or contrarian strategy is selecting winner (stocks with highest gain) or loser stocks (stocks with highest loss) and then buy or sell it based on the research result. This research employed three methods in measuring performance to select winner and loser stocks. The irst method used cross section relative return, while the second method used cross section relative return plus risk component (return divided by standard deviation), and the third method employed historical relative return instead of cross section. The result is that, all of those three methods prove that momentum strategy is effectively applicable for winner stock, so in the next period winner stock will continue to make profit, while for loser stock, it is more effective to use contrarian strategy because in the next period, loser stock will rebound and make proit after suffering from high loss